“What are we eating?” A theological-ethical analysis of the effects of food additives on human beings, especially in South Africa - L. Kretzschmar (Acta Theologica)
This article discusses Christian theological-ethical questions related to the processing of food and especially to the widespread use of food additives. First, the aims, parameters and methodology of the article are discussed. Secondly, the theme of food in the Bible is briefly explored, along with its theological implications. Thirdly, the wider cultural context of food production and processing is noted, along with the commercialisation of food. Next, the nature of food additives of various kinds, the reasons for their use and their effects on human beings are analysed to determine the extent to which their use is injurious or harmless. Throughout, and especially in the final section, a theological-ethical analysis of the use of food additives, especially in a South African context, is provided.